2011
DOI: 10.4103/2229-5119.78492
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of anti-inflammatory activities of whole plant and fruit extracts of Fragaria vesca in experimental animal models

Abstract: Background: Fragaria vesca has been used in the past for the treatment of rheumatism and gout. Material and Methods: Ethanolic extracts of fruits and the whole plant of F. vesca were prepared by the percolation method and oral toxicity testing was performed as per Organization for Economic Co-operation and Development (OECD) guidelines. The antiinfl ammatory activity against acute infl ammation was checked by the carrageenan-induced rat paw edema test, the granuloma pouch method for the subacute infl ammation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It has been reported that inflammation is a response to many physiological conditions, such as infection, thermal and/or physical injuries [27]. The inflammatory response is necessary for survival against environmental pathogens and injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that inflammation is a response to many physiological conditions, such as infection, thermal and/or physical injuries [27]. The inflammatory response is necessary for survival against environmental pathogens and injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is necessary for survival against environmental pathogens and injuries. Pain, fever and inflammation are not considered major diseases, but are common clinical manifestations associated with many fatal diseases [27]. Inflammation plays a crucial role in the pathogenesis of many auto-immune diseases [28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory response is necessary for the survival against environmental pathogens and harms. 21 Inflammation is categorized into five cardinal signs which are known as redness, swelling, heat, pain and loss of function. 22 Prostaglandins are produced by the cells which are involved in the production of pain, fever and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Natural medicine and herbs are considered to have minimum side effects and invite the scientists and researchers to find a natural medicine in order to treat pain, inflammation and pyrexia. Many plants such as Fragaria vesca, 21 Mimusops elengi linn, 22 and Melanthera scandens have recently been reported to possess analgesic, anti-inflammatory and antipyretic activities. 38 Preliminary phytochemical studies showed the presence of flavonoids and terpinoids which led to the investigation of analgesic, anti-inflammatory and antipyretic activities of C.decapetala .…”
Section: Discussionmentioning
confidence: 99%